Buried Interface Regulation with TbCl3 for Highly-Efficient All-Inorganic Perovskite/Silicon Tandem Solar Cells - Wenming Chai; Weidong Zhu; He Xi; Dazheng Chen; Hang Dong; Long Zhou; Hailong You; Jincheng Zhang; Chunfu Zhang; Chunxiang Zhu; Yue Hao (Nano-Micro Letters)
Highlights The lanthanide compound of TbCl3 improved the wettability of Me-4PACz and further enhanced crystallization, in which the additional Cl− ions passivate iodine vacancy and improve energy level alignment at buried interface. The inverted CsPbI3 PSCs with TbCl3 achieved a remarkable efficiency of 18.68% and enhanced stability in ambient air. Efficiencies of 29.40% and 25.44% were, respectively, achieved in 4T and 2T all-inorganic perovskite/silicon mechanically tandem devices.